Team Loving and Loathing - Harry A. Taute; Jeremy J. Sierra; Robert S. Heiser (University of Kansas Libraries, 2010)
The popularity of collegiate football in America is unprecedented. The fan frenzy surrounding teams, games, and the sport itself, is borderline barmy. Aptly described as the thrill of victory and the agony of defeat, fan emotions in college football are rampant; yet, research exploring such hedonic-related consumption is scant. To help close this gap, two studies, grounded in Mehrabian & Russell's (1974) pleasure, arousal, and dominance (PAD) typology of emotions, were developed to help explain collegiate football sport consumption for loved and loathed teams. Study 1 examined PAD emotional determinants of fans' purchase intentions and willingness to attend games of their favorite team. The findings indicated that the emotional dimension of arousal related positively with fans' apparel and memorabilia purchase intentions and willingness to attend games; also, the pleasure and dominance emotional dimensions related positively to purchase intentions of apparel and memorabilia, respectively. Study 2 explored PAD emotional determinants of fans' willingness to attend games involving their least favorite team. The findings revealed significant positive effects for the emotional dimensions of pleasure, arousal, and dominance on willingness to attend collegiate football games. Implications for sports marketers and future research suggestions are offered.